Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481406
|View full text |Cite
|
Sign up to set email alerts
|

Investigating self-reporting behavior in long-term studies

Abstract: Self-reporting techniques, such as data logging or a diary, are frequently used in long-term studies, but prone to subjects' forgetfulness and other sources of inaccuracy. We conducted a six-week self-reporting study on smartphone usage in order to investigate the accuracy of self-reported information, and used logged data as ground truth to compare the subjects' reports against. Subjects never recorded more than 70% and, depending on the requested reporting interval, down to less than 40% of actual app usages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…We did not find any potential link between participants' demographics and micro-usage behavior, but we must acknowledge that this might be due to our sample diversity. Despite our effort in designing the ESM to capture as much context as possible, the answer-choices could have limited users' micro-usage context [22]. Nonetheless, through our studies, we were able for the first time to specifically investigate micro-usage and the context in which it occurs.…”
Section: Limitationsmentioning
confidence: 99%
“…We did not find any potential link between participants' demographics and micro-usage behavior, but we must acknowledge that this might be due to our sample diversity. Despite our effort in designing the ESM to capture as much context as possible, the answer-choices could have limited users' micro-usage context [22]. Nonetheless, through our studies, we were able for the first time to specifically investigate micro-usage and the context in which it occurs.…”
Section: Limitationsmentioning
confidence: 99%
“…Work by Birnbaum (1999) shows that cognitive biases distort people's behavior during user studies to a high degree, resulting in all unwanted type I, II and III errors. Recently, Möller et al (2013) showed that the design of a user study has a great impact on the behavior of the participants. Besides, the context we work in drives us to investigate how intuitive interaction can be explained through neurology and behavioral sciences.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to participants not recording their activities every time they should. For example, Möller et al [71] reported that only 40-70 % of their self-report questionnaires were completed, depending on study design. Bolger et al [8] remark that participants are responsible for data gathering themselves and therefore need to be more involved and motivated.…”
Section: Self-report Methodsmentioning
confidence: 99%
“…Such methods have to meet special requirements with respect to the privacy of users [63], especially when they deal with tracking of a user's location [5]. While some researchers decided not to take privacy concerns into account [71], other approaches address social and ethical needs of users directly within the overall design process, e.g., value-sensitive design [33]. Khovanskaya et al [57] demonstrate within an empirical design study that current tools for data gathering ''do a poor job of communicating the scope of data collected […] or explicitly acknowledging the values embedded in decisions about which data are collected and how they are reflected back to the user'' [57].…”
Section: Probe Methodsmentioning
confidence: 99%